A2_9 Thunderbirds are go! - Filip, Tomasz; McMullan, Mac; Perks, Megan; Stylianou, Natalia (Physics Special Topics, 2021)
Thunderbird 2 is the largest of the flying vehicles in the Thunderbirds TV show, broadcast in the1960s. We adopted a simple mathematical model using the lift equation in order to determinewhether or not it would be capable of flying. We found that at top speed of 2240ms^-1, the valueof its lift would be 8.53×10^8N, which is greater than its weight, 4.86×10^6N, so flight would be possible.